Penerapan intervensi Manajemen Jalan Napas Terhadap Peningkatan Bersihan Jalan Napas pada Pasien TBC di Ruang Perawatan Khusus RSUD Ende - Aris Wawomeo; Maria Sekunda; Sisilia Cahyani; Syaputra Syarifudin (Poltekkes Kemenkes Kupang, 2025)
Pulmonary Tuberculosis is a disease that has the nature of airborne infection caused by the bacteria Mycobacterium Tuberculosis, this disease attacks the respiratory tract so that it can cause problems in the respiratory tract. One of the actions that can be given is airway management or airway management aimed at reducing complications related to the airway such as clearing the airway. The purpose of the case study is to be able to apply airway management to improve airway clearance in TB patients treated at Ende Regional Hospital. This study uses a case study method on patient Mr. L.N.H with Pulmonary Tuberculosis who was treated at Ende Regional Hospital on May 8-10, 2025. The results of the study were carried out based on the nursing process approach in the assessment found patient data Mr. L.N.H complained of coughing up yellow mucus for ± 1 month, decreased appetite, nausea, chest pain when coughing, body feels weak, both legs feel weak and heavy, weight loss before illness was 60 kg and when sick was 46 kg. The nursing problem that arose in Mr. L.N.H.'s case was ineffective airway clearance related to airway hypersecretion. After providing nursing care, it was found that implementing airway management could help the patient improve ineffective airway clearance.